Effects of Elevated Tropospheric Ozone Concentration on the Bacterial Community in the Phyllosphere and Rhizoplane of Rice - Ueda, Yoshiaki; Frindte, Katharina; Knief, Claudia; Ashrafuzzaman, Md; Frei, Michael (PLOS ONE, 2016)
Microbes constitute a vital part of the plant holobiont. They establish plant-microbe or microbe-microbe associations, forming a unique microbiota with each plant species and under different environmental conditions. These microbial communities have to adapt to diverse environmental conditions, such as geographical location, climate conditions and soil types, and are subjected to changes in their surrounding environment. Elevated ozone concentration is one of the most important aspects of global change, but its effect on microbial communities living on plant surfaces has barely been investigated. In the current study, we aimed at elucidating the potential effect of elevated ozone concentrations on the phyllosphere (aerial part of the plant) and rhizoplane (surface of the root) microbiota by adopting next-generation 16S rRNA amplicon sequencing. A standard japonica rice cultivar Nipponbare and an ozone-tolerant breeding line L81 (Nipponbare background) were pre-grown in a greenhouse for 10 weeks and then exposed to ozone at 85 ppb for 7 h daily for 30 days in open top chambers. Microbial cells were collected from the phyllosphere and rhizoplane separately. The treatment or different genotypes did not affect various diversity indices. On the other hand, the relative abundance of some bacterial taxa were significantly affected in the rhizoplane community of ozone-treated plants. A significant effect of ozone was detected by homogeneity of molecular variance analysis in the phyllosphere, meaning that the community from ozone-treated phyllosphere samples was more variable than those from control plants. In addition, a weak treatment effect was observed by clustering samples based on the Yue and Clayton and weighted UniFrac distance matrices among samples. We therefore conclude that the elevated ozone concentrations affected the bacterial community structure of the phyllosphere and the rhizosplane as a whole, even though this effect was rather weak and did not lead to changes of the function of the communities.